HENDERSON, Charles Lowe Inventory of documents - HENDERSON, Charles Lowe (ARCA, 2018)
Private papers of C.L. Henderson, Private Secretary for the Minister of Posts and Telegraphs [1925-1929], Labour and Social Welfare [1939], Secretary for the Labour Party [1932-1947], Senator [1939-1948]
COVERAGE 1888-1971; 5 Files; 0,11 Metre.
Keywords: HENDERSON, Charles Lowe; Inventories; Politicians; National Party